Aspects of teaching practice: education of the teacher and socialization processes - Marieta Gouvêa de Oliveira Penna (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
In this paper I present discussion on aspects of teaching practice, emphasizing learning that occurred in the socialization processes at school. It adopts, OU it is adopted the concept of teaching practice according to Gimeno Sacristán (1999), as an expression of practical schemes that mobilize the teacher and that are acquired, among other aspects, by experience. Also, it uses the concept of teacher knowledge (TARDIF, 2002).Data were collected through interviews with ten teachers in two public elementary schools in São Paulo state. Analyses have revealed that the occupation is learned in practice and that this learning is not intentional. In research, learning practices related to routines and the school operation, control practices and relationship with students and practices of organization and content selection stood out.